Digital assessment of a retentive full crown preparation—An evaluation of prepCheck in an undergraduate pre‐clinical teaching environment. (9th March 2020) - Schepke, Ulf; van Wulfften Palthe, Mariëtte E.; Meisberger, Eric W.; Kerdijk, Wouter; Cune, Marco S.; Blok, Berend
Abstract: Introduction: Acquiring practical skills is essential for dental students. These practical skills are assessed throughout their training, both formatively and summatively. However, by means of visual inspection alone, assessment cannot always be performed objectively. A computerised evaluation system may serve as an objective tool to assist the assessor. Aim: The aim of the study was to evaluate prepCheck as a tool to assess students' practical skills and as a means to provide feedback in dental education. Methods: As part of a previously scheduled practical examination, students made a preparation for a retentive crown on the maxillary right central incisor—tooth 11. Assessments were made four times by two independent assessors in two different ways: (a) conventionally and (b) assisted by prepCheck. By means of Cohen's kappa coefficient, agreements between conventional and digitally assisted assessments were compared. Questionnaires were used to assess how students experienced working with prepCheck. Results: Without the use of prepCheck, ratings given by teachers differed considerably (mean κ = 0.19), whereas the differences with prepCheck assistance were very small (mean κ = 0.96). Students found prepCheck a helpful tool for teachers to assess practical skills. Extra feedback given by prepCheck was considered useful and effective. However, some students complained about too few scanners and too little time for practice, and some believed that prepCheck is too strict. Conclusion: prepCheck can be used to assist assessors in order to obtain a more objective outcome. Results showed that practicing with feedback from both prepCheck and the teacher contributes to an effective learning process. Most students appreciated prepCheck for learning practical skills, but introducing prepCheck requires enough equipment and preparation time.